PHOTOSYNTHETIC ACTIVITY OF TOMATO IN CONTINUOUS CULTURE AND CROP ROTATION LINK AT DIFFERENT SYSTEMS OF FERTILIZATION - A. S. Virodov; O. D. Vitanov (Овощи России, 2015)
The study of net productivity of photosynthesis of tomato in continuous culture has been conducted during 2010-2013. The influence of two-year interruption by crop rotation link and different systems of fertilization on the growth of vegetative mass (g/m2 per day) was determined.